Analisis Asuhan Keperawatan Pada Pasien Dengan Gangguan Sistem Pencernaan : Post Operasi Appendectomy Dengan Masalah Keperawatan Nyeri Akut Di RSUD Kabupaten Bekasi - NURDINI, RINI; Listia, Desti (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2023)
According to data released by the Ministry of Health of the Republic of Indonesia regarding the incidence of appendicitis in Indonesia in 2016, the number of patients with appendicitis in Indonesia reached 591,819 people and increased in 2017 by 596,132 people (Soewito, 2017). The incidence of appendicitis in 2018 reached 7 of the world's population. In 2018 the incidence of appendicitis in most parts of Indonesia is still high. In Indonesia, the number of patients suffering from appendicitis is about 7% of the total population or about 179,000 people (Depkes, 2018). The author's goal is to be able to provide nursing care for post-operative appendectomy patients with acute pain nursing problems. Appendicitis is a painful swelling of the appendix with the management of appendectomy, namely surgery to remove the appendix, surgery is indicated when the diagnosis of appendicitis has been established. The research method used is a case study. Samples were taken according to the inclusion criteria of patients with post-appendectomy digestive system disorders with acute pain problems. The care was carried out for 3 days at the Bekasi District Hospital. Data was collected by: interviews, observations, physical examinations, and documentation studies. Data were analyzed narratively based on a comparison of two patients. Patient data 1 and 2 have been supportive to raise the problem of acute pain and its implementation has been implemented and there are no obstacles.